Snake venom metalloproteinases: Their role in the pathogenesis of local tissue damage - Gutiérrez, José María (2000)
The biochemical characteristics of hemorrhagic metalloproteinases isolated from snake venoms are reviewed, together with their role in the pathogenesis of the local tissue damage characteristic of crotaline and viperine snake envenomations. Venom metalloproteinases differ in their domain structure. Some enzymes comprise only the metalloproteinase domain, others have disintegrin-like and high cysteine domains and others present, besides these domains, an additional lectin-like subunit. All of them are zinc-dependent enzymes with highly similar zinc binding environments. Some metalloproteinases induce hemorrhage by directly affecting mostly capillary blood vessels. It is suggested that hemorrhagic enzymes cleave, in a highly selective fashion, key peptide bonds of basement membrane components, thereby affecting the interaction between basement membrane and endothelial cells. As a consequence, these cells undergo a series of morphological and functional alterations in vivo, probably associated with biophysical hemodynamic factors such as tangential fluid shear stress. Eventually, gaps are formed in endothelial cells through which extravasation occurs. In addition to hemorrhage, venom metalloproteinases induce skeletal muscle damage, myonecrosis, which seems to be secondary to the ischemia that ensues in muscle tissue as a consequence of bleeding and reduced perfusion. Microvessel disruption by metalloproteinases also impairs skeletal muscle regeneration, being therefore responsible of fibrosis and permanent tissue loss after snakebites. Moreover, venom metalloproteinases participate in the degradation of extracellular matrix components and play a relevant role in the prominent local inflammatory response that characterizes snakebite envenomations, since they induce edema, activate endogenous matrix metalloproteinases (MMPs) and are capable of releasing TNF-α from its membrane-bound precursor. Owing to their protagonic role in the pathogenesis of local tissue damage, snake venom metalloproteinases constitute relevant targets for natural and synthetic inhibitors which may complement antivenoms in the neutralization of these effects.